Mechatronics system design - Shetty, Devdas. (PWS, 1997)
This book is about: Mechatronics system design; Modeling and simulation of physical systems; Sensors and transducers; Actuating devices; Hardware components for mechatronics; Signals, systems and controls; Real-Time interfacing; Advanced applications in mechatronics.